(3GdZQjHjf(B: (3ZQjH GdbQBf hZQjH GdMOjKs - (3CMeO Hf eMeO Hf YHO GdQMef GdHGTGfj GdgQhj, CHh YHjO, J (B401 (3g` s ((3CMeO Hf EHQGgje Hf eMeO GdMSf GdSGhj s)
(3ChdgG (B:s
(3MQa GdXGA s
(3BNQgG (B:s
(3BNQ GdcJGH s
(3ef fSNI KGdKIs
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B210 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B150s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B4 - (3U (B89 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1209s
Keywords: (3GdMOjK h GdeUWdMs